Functional neurological disorders: effective teaching for health professionals. Issue 1 (28th June 2020) - Lehn, Alexander; Navaratnam, Dharsha; Broughton, Megan; Cheah, Vince; Fenton, Alison; Harm, Karl; Owen, Diana; Pun, Paul
Abstract : Objectives: To provide an outline for the delivery of an educational course or lecture about functional neurological disorders (FND) that is directed towards health professionals with varying clinical knowledge and to highlight the educational efficacy that can be derived from a well-designed educational platform. Method: Through multidisciplinary collaboration, a course designed to develop the skills for diagnosis and management of FND was created. Elements essential to the delivery of education are: (A) knowledge creation; (B) facilitating multidisciplinary cross-pollination; (C) listening to patients' experiences; (D) communication skills practice; (E) case studies; (F) discipline specific mentoring; (G) establishing and addressing participant learning goals and (H) developing collegial and referral networks. Changes in participants' knowledge and clinical practice were assessed via anonymous questionnaires before and after the course. Results: Dramatically improved knowledge and confidence in assessment and management of people with FND has been found both immediately following the course as well as on 6-month follow-up. Conclusion: It is possible to make real change in the understanding and management of medical and allied health clinicians working with people with FND with a low-cost intervention. Also, the development of educational networks and multidisciplinary collaboration can lead to the creation of therapeutic platforms for the diagnosis, management and advocacy of this patient group.